Analysis of Fery Irwandi's Persuasive Communication Style in Exposing Santet and Indigo Lies within Indonesian Cultural Beliefs - M. Ibnu Naufal Maskuri; Ali Ridho; Fitri Yanti; Ade Nur Istiani (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2026)
This study analyzes Fery Irwandi's persuasive communication style in the video